2009
DOI: 10.1016/j.ygeno.2008.08.002
|View full text |Cite
|
Sign up to set email alerts
|

In vitro pharmacogenomic database and chemosensitivity predictive genes in gastric cancer

Abstract: Gastric cancer is one of the most common cancers worldwide, and there are clinical caveats in predicting tumor response to chemotherapy. This study describes the construction of an in vitro pharmacogenomic database, and the selection of genes associated with chemosensitivity in gastric cancer cell lines. Gene expression and chemosensitivity databases were integrated using the Pearson correlation coefficient to give the GC-matrix. The 85 genes were selected that were commonly associated with chemosensitivity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Oligonucleotide microarray and significance analysis of microarray Oligonucleotide microarray analysis was performed with the Cancer Metastasis Research Center microarray (Jung et al 2009). In brief, the test samples (RNA isolated from each gastric cancer cell line) were labeled with Cy5 and individually co-hybridized to the Cy3-labeled reference RNA, and then incubated with a human oligo chip containing 22,740 oligonucleotide probes, which were 70 base pairs long.…”
Section: Analysis Of Median Effect Of Combined Cytotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Oligonucleotide microarray and significance analysis of microarray Oligonucleotide microarray analysis was performed with the Cancer Metastasis Research Center microarray (Jung et al 2009). In brief, the test samples (RNA isolated from each gastric cancer cell line) were labeled with Cy5 and individually co-hybridized to the Cy3-labeled reference RNA, and then incubated with a human oligo chip containing 22,740 oligonucleotide probes, which were 70 base pairs long.…”
Section: Analysis Of Median Effect Of Combined Cytotoxicitymentioning
confidence: 99%
“…Recently, spotted oligonucleotide microarrays, which use 70-base pair probes, have been applied to genome screening instead of cDNA microarrays. This technology has several advantages; it provides high quality results, avoids clone validation, tracking, and maintenance, and minimizes cross-hybridization (Jung et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…There are almost no studies that have compared the efficacy of taxane in patients with stomach cancer. In a situation where there are a series of the pre-clinical evidences that there is a discrepancy in the pharmacodynamic characteristics between the two drugs contradictory to what has been predicted, the current study might be of significance in that it would provide the baseline data for the conduct of interventional studies and clinical ones that predict the efficacy/safety of drugs in patients with progressive stomach cancer (6). Actually, we're currently conducting the clinical trials to confirm the cross-reactivity of taxanes in patients with stomach cancer and a series of interventional studies to examine single nucleotide polymporphism (SNP) of binding sites for β -tubulin or the difference in the sensitivity of inactivation enzymes.…”
Section: Discussionmentioning
confidence: 93%
“…Through V325 study, a Phase III trial, a combination treatment of cisplatin +5-FU (CF) with docetaxel (DCF) showed that the survival period and quality of life were significantly improved. The occurrence of the toxicity of Grade 3�4 in severity proposed that the treatment dose and schedule should be re-considered to accept DCF as a standard treatment modality for cases of stomach cancer (5,6). For instance, Thus-Patience et al proposed that a single use of DF except for cisplatin had an equivalent profile of the efficacy to epirubicin + cisplatin +5-FU (ECF) or DCF (2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation